Marketing Mix Analysis in Buying Halal Beauty Products in Bogor City - Muhammad Salman Al Farisi; Sawqi Saad El Hasan (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
The purpose of this study was to analysis the effect of product, price, promotion, and location on product purchasing decisions Halal Beauty Product in Bogor. This type of research is descriptive using a quantitative approach. In this study, the population used were customers/members of the Halal Beauty Product in Bogor, totaling 147 customers and a sample of 100 respondents, using purposive sampling. From the data of multiple linear regression analysis which has a coefficient of determination (Adjusted R Square) of 0.406, which means that the marketing mix has an effect on purchasing decisions of 40.6%, while the remaining 60.4% is influenced by other variables. Furthermore, hypothesis testing was carried out using the F test and t test where the F count was 39.798 with a significance value of 0.000 which was smaller than the significance level of = 0.05. Then the hypothesis is accepted, it is proven that there is a significant influence between the service marketing mix variables consisting of product (X1), price (X2), promotion (X3), location (X4), on purchasing decisions (Y). Meanwhile, based on the t-test, the most dominant variable influencing purchasing decisions is price with the largest regression coefficient value of 0.216 compared to other independent variables.